Management of Teachers — A Comparative Study of Madhya Pradesh and Karnataka - Panda, Bijoy Kumar (JOURNAL OF INDIAN EDUCATION, 2011)
Teacher management has remained very crucial for the development of education and schooling in developing countries. The dwindling resources in managing the quantum of teachers in the countries also have remained a mammoth task, as it consumed the entire chunk of resources available for the development of education. The other inputs such as school infrastructure, learning material, teaching material and qualitative improvement necessary for teaching learning and training the teachers could not be materialised. Although access to education for all has been an important input in the development of the society the necessary inputs to make it successful has remained a major challenge. To meet the manifold expansion of schooling a variety of teachers such as contract teachers, community teachers, temporary teachers, para-teachers and many cadres of teachers have entered the arena of education system. However, these quick remedies were able to meet the demand of schools by bringing more and more children into the ambit of education. A big question that still remains unanswered is that by mere provision of teachers in the schools will it be able to improve the effectiveness of schools and increase their efficiency? As there is a vast ground work needs to be done to enable the teachers to perform efficiently, issues such as qualified teachers, training and retraining and service condition of teachers, promotion, facilities of housing and remuneration —all play a great role in motivating the teachers and to perform effectively. Although the governments have been developing policies for teachers but the implementation of such practices are seldom followed which has resulted in poor performance as well as unrest among teachers. The present comparative study was undertaken to understand some of the issues relating to the management of teachers which can have direct bearing on effective functioning of schooling and education system. The study was conducted in the states of Madhya Pradesh and Karnataka and focused on support being extended by the administration to primary teachers in order to facilitate them to perform efficiently.